Establishment and application of a novel patient-derived KIAA1549: BRAF-driven pediatric pilocytic astrocytoma model for preclinical drug testing - Selt, Florian; Buhl, Juliane; Sahm, Felix; Capper, David; Korshunov, Andrey; Usta, Diren; Brabetz, Sebastian; Ridinger, Johannes; Ecker, Jonas; Oehme, Ina; Bächli, Heidi; Deimling, Andreas von; et al. (OncoTarget, 2017)
Pilocytic astrocytoma (PA) is the most frequent pediatric brain tumor. Activation of the MAPK pathway is well established as the oncogenic driver of the disease. It is most frequently caused by KIAA1549:BRAF fusions, and leads to oncogene induced senescence (OIS). OIS is thought to be a major reason for growth arrest of PA cells in vitro and in vivo, preventing establishment of PA cultures. Hence, valid preclinical models are currently very limited, but preclinical testing of new compounds is urgently needed. We transduced the PA short-term culture DKFZ-BT66 derived from the PA of a 2-year old patient with a doxycycline-inducible system coding for Simian Vacuolating Virus 40 Large T Antigen (SV40-TAg). SV40-TAg inhibits TP53/CDKN1A and CDKN2A/RB1, two pathways critical for OIS induction and maintenance. DNA methylation array and KIAA1549:BRAF fusion analysis confirmed pilocytic astrocytoma identity of DKFZ-BT66 cells after establishment. Readouts were analyzed in proliferating as well as senescent states, including cell counts, viability, cell cycle analysis, expression of SV40-Tag, CDKN2A (p16), CDKN1A (p21), and TP53 (p53) protein, and gene-expression profiling. Selected MAPK inhibitors (MAPKi) including clinically available MEK inhibitors (MEKi) were tested in vitro. Expression of SV40-TAg enabled the cells to bypass OIS and to resume proliferation with a mean doubling time of 45h allowing for propagation and long-term culture. Withdrawal of doxycycline led to an immediate decrease of SV40-TAg expression, appearance of senescent morphology, upregulation of CDKI proteins and a subsequent G1 growth arrest in line with the re-induction of senescence. DKFZ-BT66 cells still underwent replicative senescence that was overcome by TERT expression. Testing of a set of MAPKi revealed differential responses in DKFZ-BT66. MEKi efficiently inhibited MAPK signaling at clinically achievable concentrations, while BRAF V600E- and RAF Type II inhibitors showed paradoxical activation. Taken together, we have established the first patient-derived long term expandable PA cell line expressing the KIAA1549:BRAF-fusion suitable for preclinical drug testing.
Published online: December 17, 2016
Gesehen am 04.07.2018